Association of hypertension, type 2 diabetes mellitus and dyslipidemia with the duration of inpatient treatments and recurrence of schizophrenia - Lamadé, Eva; Özer, Nicole; Schaupp, Bernhard; Krumm, Bertram; Deuschle, Michael; Häfner, Sibylle (Journal of psychosomatic research, 2023)
Objective - People with schizophrenia have an increased cardiovascular risk with higher mortality than the general population. Only a few studies have investigated the impact of cardiovascular risk on the later course of schizophrenia. This study aims to explore the association of cardiovascular risk factors, as detected during an index inpatient treatment for schizophrenia, with the duration of psychiatric inpatient treatments and number of inpatient admissions in the subsequent 10 years, in patients with schizophrenia. - Methods - Cardiovascular risk factors of 736 patients with schizophrenia, identified through retrospective chart review, were assessed by hypertension, type 2 diabetes mellitus and dyslipidemia during an index inpatient stay. The duration of inpatient treatments, assessed by the total duration of psychiatric inpatient treatments in days, and the number of inpatient admissions, over the next 10 years were assessed and analyzed for an association with cardiovascular risk factors. - Results - Hypertension associated with longer duration of inpatient treatments and higher number of inpatient admissions. Type 2 diabetes mellitus and dyslipidemia associated with a higher number of psychiatric inpatient treatments. Hypertension remained significantly associated with the duration of inpatient treatments (β = 0.174; p < 0.001) and the number of inpatient treatments (β = 0.144; p < 0.001), when adjusting for age, sex and BMI. - Conclusion - Out of the investigated cardiovascular risk factors documented during an index inpatient stay for schizophrenia, only hypertension associated with an increased duration of in-hospital stay and an increased number of re-hospitalizations during the subsequent ten years when adjusting for confounders. Screening for hypertension should be considered in all patients with schizophrenia.
Online verfügbar: 4. Juli 2023, Artikelversion: 14. Juli 2023
Gesehen am 27.09.2023